Bi+ adults' daily wellbeing: The roles of relationship status and partner gender. Issue 2 (14th January 2022) - Vilkin, Ellora; Davila, Joanne; Dyar, Christina; Feinstein, Brian A.
Abstract: This study examined whether relationship involvement and partner gender were associated with between‐person differences and within‐person fluctuation in positive and negative affect and alcohol use among people who are attracted to more than one gender or regardless of gender (e.g., bisexual, pansexual, queer; bi+). One hundred and ninety‐eight bi+ individuals ( M age 26.97; 73.1% non‐Latinx White) completed a 28‐day diary study. Multilevel regression analyses modeled between‐person differences in daily affect and alcohol use as a function of relationship status and partner gender. ANCOVAs were conducted to examine differences in within‐person fluctuation. Results partially support past findings that relationship involvement may not confer benefits for bi+ people and that mixed‐gender partnerships could be particularly challenging. Future research directions are discussed.